Recent advances in the chromatin-based mechanism of FLOWERING LOCUS C repression through autonomous pathway genes - Kyung, Jinseul; Jeon, Myeongjune; Lee, Ilha (Frontiers in Plant Science, 2022)
Proper timing of flowering, a phase transition from vegetative to reproductive development, is crucial for plant fitness. The floral repressor FLOWERING LOCUS C (FLC) is the major determinant of flowering in Arabidopsis thaliana. In rapid-cycling A. thaliana accessions, which bloom rapidly, FLC is constitutively repressed by autonomous pathway (AP) genes regardless of photoperiod. Diverse AP genes have been identified over the past two decades, and most of them repress FLC through histone modifications. However, the detailed mechanism underlying such modifications remains unclear. Several recent studies have revealed novel mechanisms to control FLC repression in concert with histone modifications. This review summarises the latest advances in understanding the novel mechanisms by which AP proteins regulate FLC repression, including changes in chromatin architecture, RNA polymerase pausing, liquid–liquid phase separation, and ncRNA-mediated gene silencing. It also discusses how each mechanism is coupled with histone modifications in FLC chromatin.